Managing pregnancy in ewes (Czech Journal of Multidisciplinary Innovations, 2022)
Pregnancy is generally 150 days (five months). The majority of foetal growth occurs in the final 60 days, however, setting up effective nutrient transfer from the ewe to the foetus occurs with udder and placental development in the first trimester of pregnancy. Most of the wool follicle development occurs in the second and third trimesters and can be significantly affected by nutrition. The nutrition of the ewe during pregnancy affects the liveweight and the wool production of the progeny over its lifetime. The ewe,s ability to survive and provide for the lamb over the difficult lambing period is also greatly affected by nutrition, will also affect her wool quality and quantity